Model Pendidikan Komunikasi Iman di Sekolah Menengah Kejuruan Negeri di Kota Jakarta Pusat - Lusia Rahajeng (Jurnal Pendidikan Kristen dan Ilmu Teologi Marturia, 2023)
AbstractIndonesian society, both demographically and sociologically, is a diverse society. The characteristics that characterize the nature of this diversity are the presence of language, race (ethnic), religious beliefs and other cultural practices. This cultural diversity is an invaluable asset of the nation, but at the same time cultural diversity can collapse or be a divisive one for a country. This cultural diversity is often used as a trigger for racial, religious, ethnic, and intergroup (SARA) conflicts. When children enter the school education level, the teachings of tolerance and respect for differences must be instilled as early as possible. Therefore, this study aims to describe how the faith communication education model can be accepted as an educational model to teach giving meaning to pluralism in Indonesia. The method used is a qualitative research method with a literature review approach. The result of the research is that teachers and students can apply the faith communication education model as a learning model for Christian religious education in schools. Abstrak Masyarakat Indonesia baik dari segi demografis maupun sosiologis merupakan masyarakat yang beragam. Ciri-ciri yang mencirikan sifat keanekaragaman ini adalah adanya bahasa, ras (suku), keyakinan agama dan praktik budaya lainnya. Keanekaragaman budaya adalah peninggalan bangsa yang tidak ternilai harganya, namun pada saat yang sama keragaman budaya dapat runtuh atau menjadi pemecah belah suatu negara. Keberagaman budaya ini sering dijadikan sebagai pemicu konflik ras, agama, suku, dan antargolongan (SARA). Ketika anak memasuki jenjang pendidikan sekolah, ajaran toleransi dan menghargai akan perbedaan harus ditanamkan sedini mungkin. Oleh karena itu, penelitian ini bertujuan untuk mendeskripsikan bagaimana model pendidikan komunikasi iman dapat diterima sebagai model pendidikan untuk mengajarkan memberi makna terhadap pluralisme di Indonesia. Metode yang digunakan yakni metode penelitian kualitatif dengan pendekatan literature review. Hasil riset yaitu guru serta peserta didik bisa mempraktikkan model pembelajaran komunikasi iman sebagai salah satu model pendidikan pembelajaran agama Kristen di sekolah.